Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.23736/s1973-9087.23.07772-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe secretion retention: a predictor of decannulation outcome in severe brain injury patients with tracheostomy

Abstract: BACKGROUND Identifying accurate predictors of decannulation outcome is essential to ensure safe and timesaving decannulation. Studies indicated hypopharyngeal secretion retention is closely associated with compromised airway protection and patients with it are less likely to be decannulated. However, data verifying the link between secretion retention and decannulation outcome are lacking. AIM The aim of this study was to identify the association between hypopharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The trauma and esophageal anastomosis at the neck after MIE would increase secretions. The poor pharyngeal clearance of secretions could lead to laryngeal penetration and aspiration, and aspiration pneumonia [9,10] and the patients of MIE in the early stages of anesthesia recovery usually have no su cient airway protection. Additionally, previous studies have reported severe secretion retention in patients with a tracheostomy tube than in those without.…”
Section: Introductionmentioning
confidence: 99%
“…The trauma and esophageal anastomosis at the neck after MIE would increase secretions. The poor pharyngeal clearance of secretions could lead to laryngeal penetration and aspiration, and aspiration pneumonia [9,10] and the patients of MIE in the early stages of anesthesia recovery usually have no su cient airway protection. Additionally, previous studies have reported severe secretion retention in patients with a tracheostomy tube than in those without.…”
Section: Introductionmentioning
confidence: 99%